Pengelolaan arsip statis di Dinas Kearsipan Daerah Provinsi Sumatera Selatan - Eka Apriyani; Dinda Safira; Rhoni Rodin (IAIN Padangsidimpuan, 2020)
This study aims to determine the management of static archives in the South Sumatra Archives Service. The research method used is a qualitative approach using a survey design type to obtain valid data by conducting observations and interviews directly to the speakers and the results using descriptive analysis. Management of static records carried out at the South Sumatra Archives Service covers the activities of collecting static records, acquisition of static records, archival search lists (DPA), management of static records, maintenance of static records, access or static archive retrieval systems and archival information systems. In the management of static records carried out at the South Sumatra Archives Service, it is quite good, but it is still constrained by human resources, funds and lack of awareness of agencies under the archives service that must submit static records that have a use and historical value so that this becomes one of the obstacles in managing records in the South Sumatra Regional Archives Service.